Relationship Between Forced Vital Capacity and Framingham Cardiovascular Risk Score Beyond the Presence of Metabolic Syndrome: The Fourth Korea National Health and Nutrition Examination Survey. Issue 47 (November 2015) - Kang, Hyung Koo; Park, Hye Yun; Jeong, Byeong-Ho; Koh, Won-Jung; Lim, Seong Yong
Abstract : Abstract: Impaired lung function is a risk factor for cardiovascular (CV) events. However, it has not been well established whether FVC reduction even within normal range is associated with cardiovascular disease (CVD) risk and whether reduced FVC is an independent relationship of CVD irrespective of metabolic syndrome. Thus, we aimed to explore the relationship between FVC and CV-event risk using the FRS beyond the presence of metabolic syndrome or abdominal obesity in a representative Korean population based on data from the nationwide Korea National Health and Nutrition Examination Survey (KNHANES IV). The study population included 9688 subjects ≥ 30 years of age with no previous diagnosis of CVD and obstructive lung disease. Using a logistic regression model and area under the curve (AUC) analysis, we evaluated the relationship between FVC quintiles and CV-event risk using the Framingham Risk Score (FRS; ≥ 10% or ≥ 20%). In addition, we examined the effect of FVC on CV-event risk based on the presence of metabolic syndrome (MetS) and abdominal obesity. After adjusting for covariates, comparison of subjects in the lowest FVC (% pred) quintile (Q1) with those in the highest quintile (Q5) yielded an odds ratio (OR) of 2.27 (95% CI, 1.91–2.71) for intermediate and high risk, and 2.89 (95% CI, 2.31–3.61) for high risk. The ORs for cardiovascular risk using FRS also increased irrespective of the presence of abdominal obesity and MetS without significant interaction. Furthermore, the addition of FVC status to MetS status and abdominal obesity status significantly increased the AUC of the model predicting CV-event risk ( P  < 0.001 and P  < 0.001). Our study demonstrates that FVC is inversely associated with 10-year CV-event risk, irrespective of MetS and abdominal obesity in the general population without obstructive lung disease. Furthermore, the addition of FVC to MetS or abdominal obesity increased prediction of CVD event risks, implying a potential role of FVC to predict CV events.